Association of immune checkpoint inhibitors with respiratory infections: A review. (November 2020) - Hamashima, Ryosuke; Uchino, Junji; Morimoto, Yoshie; Iwasaku, Masahiro; Kaneko, Yoshiko; Yamada, Tadaaki; Takayama, Koichi
Highlights: Use of immune checkpoint inhibitors are now being expanded to many cancer types. Different mechanisms of action of common anticancer drugs allow unique side effects. Evidence for infectious diseases as immune-related adverse events is often unclear. Use of ICIs involves immune mechanisms and the effect on pathogens differs. Abstract: Treatment with immune-checkpoint inhibitors (ICIs) has shown efficacy against a variety of cancer types. The use of anti PD-1, anti PD-L1, and anti CTLA-4 antibodies is rapidly expanding. The side effects of ICIs are very different from conventional cytocidal anticancer and molecular target drugs, and may extend to the digestive organs, respiratory organs, thyroid gland, pituitary gland, skin, and others. Although the details of these adverse events are becoming increasingly apparent, much is unknown regarding the effects and adverse events related to infections. This review focuses specifically on the impact of ICIs on respiratory infections. The impact of ICIs on pathogens varies depending on the significance of the role of T-cell immunity in the immune response to the specific pathogen, as well as the different modes of infection (i.e., acute or chronic), although the impact of ICIs on the clinical outcome of infections in humans has not yet been well studied. Enhanced clearance of many pathogens has been shown because immune checkpoint inhibition activates T cells. In contrast, reactivation of tuberculosis associated with ICI use has been reported, and therefore caution is warranted. In COVID-19 pneumonia, ICI administration may lead to exacerbation; however, it is also possible that ICI may be used for the treatment of COVID-19. It has also been shown that ICI has potential in the treatment of intractable filamentous fungal infections. Therefore, expanded clinical applications are expected.